2020
DOI: 10.3357/amhp.5656.2020
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Pain in Commercial Airline Pilots

Abstract: BACKGROUND: In their working life, airline pilots are exposed to particular risk factors that promote nonspecific low back pain (LBP). Because of the varying incidence internationally, we evaluated the point prevalences of acute, subacute, and chronic nonspecific LBP, as well as the current prevalences in German airline pilots. Furthermore, we compared the prevalence to the general German population and to European counterparts.METHODS: An anonymous online survey of 698 participating German airline pilots was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Some evidence has indicated an elevated incidence for melanoma and kidney disease compared to the general population 1,4 . Further, noteworthy risk prevalence has been reported for back pain, 9 obesity, 2,5 metabolic syndrome, 10 physical inactivity, 8,11 poor sleep, 11,12 and depressive symptoms in pilots 13 …”
mentioning
confidence: 99%
“…Some evidence has indicated an elevated incidence for melanoma and kidney disease compared to the general population 1,4 . Further, noteworthy risk prevalence has been reported for back pain, 9 obesity, 2,5 metabolic syndrome, 10 physical inactivity, 8,11 poor sleep, 11,12 and depressive symptoms in pilots 13 …”
mentioning
confidence: 99%
“…Moreover, in a cross-sectional study, Runeson-Broberg et al [ 35 ] identified having a high work demand, being female, having low social support, and suffering from psychosocial stress as risk factors for musculoskeletal symptoms. Albermann et al [ 36 ], in a cross-sectional study, identified a high prevalence of chronic low back pain among pilots (82.7%) and a significant association with low back pain in those who had a total flight time of more than 600 h in the previous 12 months ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Health promotion interventions for pilots aimed at improving nutrition, PA, and sleep behaviors are likely to produce positive outcomes toward common perceived work-related wellbeing issues expressed by pilots, including; sleep difficulties [ 9 ], psychological fatigue [ 45 ], musculoskeletal issues [ 46 ], digestive problems [ 47 ], and may mitigate NCD risks [ 48 ]. Indeed, some evidence suggests that those who achieve health recommendations for sleep, PA and fruit and vegetable intake are more likely to achieve optimal health than those engaging in zero to one healthy behavior [ 49 ].…”
Section: Introductionmentioning
confidence: 99%